A Mind that Forgets: Memory and Forgetting- Its Disorders and Scope of Homoeopathy (Homoeopathy for All, 2021)
Memory is the ability to take in information, store it, and recall it at a later time. In psychology, memory is broken into three stages: encoding, storage, and retrieval. Problems can occur at any stage of the process. Memory disorders can progressive, including Alzheimer's disease, or they can be immediate including disorders resulting from head injury. Homoeopathy finds a wide variety of its application in this kind of memory disorders. Where the process take place by converting symptoms into rubric and later selecting the suitable drug which covers the symptoms.
Keywords: symptoms; encoding; Alzheimer's disease